The Immersive Internet
XX, 264 p.
Keywords: Collecting short thought pieces by some of the leading thinkers on the emerging 'Immersive Internet', Power and Teigland's book questions what a more immersive and intimate internet – based on social media, augmented reality, virtual worlds, online games, 3D internet and beyond – might mean for society and for each of us.